A new wrinkle: Umbilical cord management (how, when, who). Issue 5 (October 2018) - Katheria, Anup; Hosono, Shigeharu; El-Naggar, Walid
Abstract: In the past five years, umbilical cord management in both term and preterm infants has come full circle, going from the vast majority of infants receiving immediate cord clamping to virtually all governing organizations promoting placental transfusion, mainly in the form of delayed cord clamping (DCC). Placental transfusion refers to the transfer of more blood components to the infant during the first few minutes after birth. The different strategies for ensuring placental transfusion to the baby include delayed (deferred) cord clamping, milking of the attached cord before clamping, and milking of the cut cord. In this review, we address the current evidence to date for providing placental transfusion in different circumstances and the methods for implementation. We also highlight the gaps in knowledge and areas for future research.